2018
DOI: 10.3390/s18103538
|View full text |Cite
|
Sign up to set email alerts
|

Realization and Technology Acceptance Test of a Wearable Cardiac Health Monitoring and Early Warning System with Multi-Channel MCGs and ECG

Abstract: In this work, a wearable smart clothing system for cardiac health monitoring with a multi-channel mechanocardiogram (MCG) has been developed to predict the myo-cardiac left ventricular ejection fraction (LVEF) function and to provide early risk warnings to the subjects. In this paper, the realization of the core of this system, i.e., the Cardiac Health Assessment and Monitoring Platform (CHAMP), with respect to its hardware, firmware, and wireless design features, is presented. The feature values from the CHAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 34 publications
(47 reference statements)
0
47
0
1
Order By: Relevance
“…In an observational study of 45 heart failure patients wearing a seismocardiography patch, graphic analysis was able to differentiate between compensated and decompensated patients' responses to a 6-min walk test and importantly within-subject improvements correlated with changes in seismocardiography measurements [55]. Furthermore, incorporating measurements from multiple seismocardiogram sensors integrated into a wearable vest, algorithms were able to predict real-time left ventricular ejection fraction [56]. Multiple electrodes imbedded in smart textiles could allow extraction of information such as heart rate, heart rate variability, respiratory rate and thoracic impedance, comparable with device-based algorithms such as HeartLogic™ [43•].…”
Section: Technology In Development For Early Detection Of Hf Decompenmentioning
confidence: 99%
“…In an observational study of 45 heart failure patients wearing a seismocardiography patch, graphic analysis was able to differentiate between compensated and decompensated patients' responses to a 6-min walk test and importantly within-subject improvements correlated with changes in seismocardiography measurements [55]. Furthermore, incorporating measurements from multiple seismocardiogram sensors integrated into a wearable vest, algorithms were able to predict real-time left ventricular ejection fraction [56]. Multiple electrodes imbedded in smart textiles could allow extraction of information such as heart rate, heart rate variability, respiratory rate and thoracic impedance, comparable with device-based algorithms such as HeartLogic™ [43•].…”
Section: Technology In Development For Early Detection Of Hf Decompenmentioning
confidence: 99%
“…The authors expected that wearable technology in the field of ergonomics can have cost effective risk assessment and economical solutions in the future. The study from Lin et al [13] presented the design of a wearable cardiac health monitoring platform, implemented it as wearable smart clothing system with multi-channel mechanocardiograms and electrocardiograms measurements, and evaluated the usability of the system using technology acceptance model. The analysis and the results of the study showed the positive attitude of subjects for using this wearable system in providing early risk warnings.…”
Section: Summary Of Special Issue Papersmentioning
confidence: 99%
“…Telemedicine) (Ha et al 2018 ). Wearable systems are mainly used for monitoring the symptoms and status of patients, follow up, telemedicine, monitoring of nursing and medical team systems, surgery robots, and many other systems (Lin et al 2018 ; Majumder and Deen 2019 ). However, wearable sensors have received tremendous attention over the past decade, mainly concentrated in the healthcare industry.…”
Section: Introductionmentioning
confidence: 99%